A systematic review and meta-analysis of cemented and uncemented bipolar hemiarthroplasty for the treatment of femoral neck fractures in elderly patients over 60 years old - Fu, Mengyu; Shen, Jieliang; Ren, Zhoukui; Lv, Yingwen; Wang, Jiangang; Jiang, Wei (Frontiers in Medicine, 2023)
Background Currently, whether cement can be applied in bipolar hemiarthroplasty to treat femoral neck fractures (FNFs) in elderly patients is controversial. The aim of this systematic review and meta-analysis was to compare the effectiveness and safety of cemented bipolar hemiarthroplasty (CBH) versus uncemented bipolar hemiarthroplasty (UCBH) in the treatment of FNFs among elderly patients over 60 years old. Results A total of 6 randomized controlled trials (RCTs) and 9 observational studies were included in this analysis, with 33118 patients (33127 hips). Results of the meta-analysis indicated that the operation time (MD=13.01, 95%CI[10.79, 15.23]), intra-operative blood loss (MD=80.56, 95%CI[60.90, 100.21]), incidence of heterotrophic ossification (OR=2.07, 95%CI[1,14, 3.78]), were increased in the CBH group but the incidence of intra-operative fracture (OR=0.24, 95%CI[0.07, 0.86]), periprosthetic fracture (OR=0.24, 95%CI[0.18, 0.31]), aseptic loosening of prosthesis (OR=0.20, 95%CI[0.09, 0.44]), wound infection (OR=0.80, 95%CI[0.68, 0.95]) and re-operation rates (OR=0.61, 95%CI[0.54, 0.68]) were lower in CBH group comparison with the UCHB group. However, there were no significant differences in residual pain, length of hospital stay, prosthetic dislocation, prosthetic subsidence (＞5mm), acetabulum erosion, revision, pulmonary infection, pulmonary embolism, urinary tract infection, deep venous thrombosis, decubitus, cardiovascular accidents (arrhythmia/myocardial infarction) and respiratory failure between the two groups. In terms of mortality, perioperative mortality (within 72 hours) (OR=2.39, 95%CI[1.71, 3.32]) and 1-week mortality postoperatively (OR=1.22, 95%CI[1.05, 1.41]) in CBH group was higher compared with the UCBH group, but there was no significant difference in mortality at 1 month, 3 months, 1 year and 2 years postoperatively between CBH group and UCBH group. Conclusion This meta-analysis found that elderly patients over 60 years old with FNFs who underwent CBH had longer operation time, higher intra-operative blood loss, incidence of heterotrophic ossification and mortality within 72 hours of operation and at 1-week postoperatively, but lower incidence of periprosthetic fracture, aseptic loosening of prosthesis, intra-operative fracture, wound infection and re-operation. Other outcomes were not significantly different between the two groups.